2015
DOI: 10.1037/tra0000022
|View full text |Cite
|
Sign up to set email alerts
|

Betray my trust, shame on me: Shame, dissociation, fear, and betrayal trauma.

Abstract: Recent research suggests that betrayal is a fundamental dimension of trauma that may be a major factor contributing to posttraumatic distress (Freyd & Birrell, 2013). In the current study using a college student sample of female trauma survivors, (N = 124; 79% Caucasian; mean age = 20.40, SD = 3.60), we examined the contribution of high- and low-betrayal trauma history to shame, dissociation, and fear responses to threat. We hypothesized that (a) overall, shame and dissociation would be higher following interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…Furthermore, a recent study showed that a high betrayal trauma history (i.e. survivors of abuse perpetrated by someone, trusted, close or depended on) increases the risk of developing a wide range of dissociative symptoms including depersonalization and derealization among female college students following exposure to interpersonal threat images (Platt & Freyd, 2015). Indeed, this is mirrored by the high proportion of individuals with the D-PTSD found in the incest sample compared to the other included samples (Hansen et al, 2016b).. Future research is therefore needed to shed more light on this and it is important that this research seeks to investigate the relationship between risk factors and D-PTSD using multivariate techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study showed that a high betrayal trauma history (i.e. survivors of abuse perpetrated by someone, trusted, close or depended on) increases the risk of developing a wide range of dissociative symptoms including depersonalization and derealization among female college students following exposure to interpersonal threat images (Platt & Freyd, 2015). Indeed, this is mirrored by the high proportion of individuals with the D-PTSD found in the incest sample compared to the other included samples (Hansen et al, 2016b).. Future research is therefore needed to shed more light on this and it is important that this research seeks to investigate the relationship between risk factors and D-PTSD using multivariate techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Rugens and Terhune (2013) found that those participants who had a trait propensity toward dissociation reported more dissociation immediately after exposure to guilt cues than after exposure to general negative cues and neutral cues. Such findings have led to the suggestion that dissociative phenomena may have affect regulation value, reducing the emotional impact of painful feelings by creating psychological distance via experiences such as depersonalization, derealization, intense absorption in selected stimuli, confusion about oneself, losing self-reference, and amnesia (e.g., Platt & Freyd, 2015).…”
mentioning
confidence: 99%
“…Yet leaving the institution is not only to protect against betrayal. Many APA members may have experienced a sense of shame at the actions of APA and/or their own failure to do more sooner; in fact, shame is a common response to betrayal and is associated with withdrawing from reminders of one's perceived transgressions (Platt & Freyd, 2015). Those who do remain members may experience a sense of mistrust or disconnection from APA and be uncertain how to navigate continued relationships.…”
Section: The Harm Of Apa's Institutional Betrayalsmentioning
confidence: 99%